The epidemiology of low back pain and injury in dance: A systematic review - Swain, C. T. V.; Bradshaw, E. J.; Ekegren, C. L.; Whyte, D. G. (Journal of Orthopaedic & Sports Physical Therapy, 2019)
Study Design: Systematic review. Background: Dance is a physical pursuit that involves loading the spine through repetitive dynamic movements and lifting tasks. As such, low back pain (LBP) and low back injury (LBI) have been identified as common health problems within contemporary dance and classical ballet populations. However, clarity regarding the experience of LBP and LBI in dance is lacking. Objectives: To systematically review and synthesize the epidemiology on LBP and LBI in dance populations. Methods: A comprehensive search of six electronic databases, back catalogues of dance science specific journals, reference lists of relevant articles, and a forward citation search were performed. Results: Fifty full text articles were included in the final review. There was considerable methodological heterogeneity amongst the included studies. The median (range) point, yearly, and lifetime prevalence of LBP was 27% (17 - 39%), 73% (41 - 82%), and 50% (17 - 88%) respectively. The lower back contributed to 11% (4 - 22%) of time loss and 11% (5 - 23%) of medical attention injuries. Conclusion: Dancers are vulnerable to LBP and injury. The use of definitions that are sensitive to the complexity of LBP and LBI would facilitate improved understanding of the problem within dance, would inform healthcare strategies, and allow for monitoring of LBP specific intervention outcomes.